Grand Challenges for Catalytic Remediation in Environmental and Energy Applications Toward a Cleaner and Sustainable Future - Yentekakis, Ioannis V.; Dong, Fan (Frontiers in Environmental Chemistry, 2020)
This article presents and discusses several hot topics and current trends for Catalytic Remediation in processes of significant environmental and energy importance. These topics seem to have the potentiality to guide future endeavors and synergistic interactions of several scientific disciplines, not limited to the chemists' and chemical engineers' communities, toward a common goal of great importance that is “Toward a cleaner (green) and sustainable future.” Under this context, the following main topics and grand challenges are addressed here: (i) Further in-depth understanding and fine-tuning surface chemistry, catalytic activity, promotion, and stability, (ii) Current Advances and future perspectives in catalytic remediation of mobile and stationary sources' emissions (elimination of NOx, N2O, VOCs, CO, soot, etc.)–“Emissions Control Catalysis,” (iii) Clean energy production related catalytic reactions – H2 production and purification, (iv) Catalytic CO2 hydrogenation (CO2 utilization/recycling), (v) Photo-electro-Catalysis: Managing the effects of co-existence and mixtures of multiple pollutants in realistic conditions; understanding the interfacial reaction mechanism between reactants and photocatalysts; selectivity enhancement and intermediates/byproducts inhibition; development of catalysts with abundant and stable electrochemical active sites; precise identification of the time-resolved reaction information at the interface. Several sub-topics between them are also highlighted.